Italian cultural policy: conclusions for Russia - M. S. Andreykina; D. L. Morozova (Управление)
The article analyses current public management and funding practices of cultural organisations in Italy by using comparative and statistical analysis. The structure of the sector’s governing bodies and approaches to budgeting for culture at national level have been explored. Trends in decreasing funding from provincial, regional and local budgets have been identified. The status, legislative and institutional conditions for the emergence of Italy’s unique multichannel cultural financing system have been described. An analysis of the Italian museum system’s reform has been presented. The activities of private opera foundations have been discussed in detail. The main similarities between Russian and Italian cultural policies have been described. These are the drive to expand the boundaries and activities associated with the cultural sector, the significant burden on local and regional authorities in the field of cultural heritage preservation, the “quantitative approach” and the application of financial performance indicators to assess cultural organisations performance.The article’s scientific novelty lies in the complex approach to the study of Italian cultural policy using the criteria proposed by D. Montias and A. I. Glagolev, and in the study of the activities of Italian opera foundations and museums, which had not previously been sufficiently covered in the Russian and foreign literature. The prospect of the topic, the practical significance and relevance of the research are due to the need to implement regulations in Russia which set a course for the creation of a multi-channel system of funding and a broad understanding of the cultural sector, and ensuring inter-agency and inter-regional cooperation between the authorities in the implementation of cultural policy.The article analyses a wide range of financial support mechanisms for culture, most of which are named in the “Strategy of State Cultural Policy of Russia as Targets by 2030”, while Italy has accumulated considerable experience in this area for several decades.